Natural analogies among organizational culture models - Kiril Dimitrov (Vanguard Scientific Instruments in Management, 2012)
The current article presents and justifies the wise use of natural analogies in teaching Firm culture at the Universities and in consulting activities in organizations, associated with necessary study of an existing firm culture, before undertaking change management initiatives that are intended to ensure lasting effects. The meanings and structures of widely used cultural metaphors such as an iceberg, a tree, an onion, a water-lily, an apple and an egg are described and analyzed here.
Keywords: M14; L1; L2; Z1; 330; organizational culture; firm culture; natural analogies; common metaphors; cultural levels